Effects of soybean residue addition on yogurt quality: physicochemical, functional, and sensory properties: Enhancing Yogurt Quality with the Addition of Soy Residue - Zhang, Ying; Kim, Jisuk; Song, Ka-Young; Kim, Yookyung (Progress in Nutrition, 2024)
Okara contained bioactive substances, including isoflavones and other natural polyphenols with strong antioxidant activity. We intended to produce better quality yogurt by adding okara; thus, our types of yogurt were prepared: yogurt without additives (control; C), with soy powder (SY), with okara (OY), and with roasted okara (ROY). The yogurt was analyzed for physicochemical (total Lactobacillus, titratable acidity, whey separation, and viscosity), functional (isoflavone, total phenols, and antioxidant capacity), and sensory properties. The addition of okara increased the total Lactobacillus count. The OY sample (35.80 × 1012 CFU/g) had a total Lactobacillus count that was 18 times higher than that of C (2.80 × 1012 CFU/g). Furthermore, the isoflavone content was the highest in OY at 18.15 mg/kg. The total phenol content and DPPH radical-scavenging capacity were as follows in the order of highest to lowest: SY, ROY, OY, and C. The changes in viscosity during fermentation showed the fastest rate in OY, which seemed to shorten the fermentation time from 8 h to 6 h. No significant difference in the whey separation rate was observed in OY (20.0–20.1%) over 15 days of storage. Additionally, the OY (4.16) and ROY (4.34) samples had better overall acceptability scores than SY (1.78). Okara is an effective additive that can be used to improve the total Lactobacillus count and antioxidant capacity of yogurt, and extend its shelf life.